Typical design of a reclaimed spiral heat exchanger - الغدا عفراء; أيوب عيسى حسن (Latakia University Journal -Engineering Sciences Series, 2023)
To use a heat exchanger in a thermal array, there must be a temperature difference between the two fluids, to ensure heat transfer. This temperature difference can be reduced by using a larger size heat exchanger, but this will increase both size and costs. The considerations of these two trends are very important in the integrated engineering design of the exchanger, not only in terms of performance characteristics, but also in terms of the economic cost of the system. The way the reclaimed spiral heat exchanger was designed was to reduce fuel consumption within the combustion chamber and thus reduce harmful gases emitted to the external environment. Through modeling using Matlab and because of using a helical heat exchanger model, the amount of increase in thermal yield was about 10%. In addition to reducing the proportion of fuel consumed within the combustion chamber from 8,424 kg⁄h to 5,616 kg⁄h, thus, this leads to reducing the proportion of gases to the external environment that cause global warming, and this is considered an important factor in preserving the environment.